IoT-based Running Time Monitoring System for Machine Preventive Maintenance Scheduling - Sitompul, Erwin; Rohmat, Agus (ELKHA : Jurnal Teknik Elektro, 2021)
Machines are valuable assets that need to be protected from damage and failure through proper maintenance measures. This paper proposes a system that automatically monitors the running time of machines and sends notifications regarding their preventive maintenance (PM) schedules. The system core consists of a programmable logic controller (PLC) and a human machine interface (HMI). The HMI is connected to an online platform via internet connection provided by a router, so that the monitoring result can be accessed via Android smartphone or laptop/PC. This IoT-based running time monitoring system (IRTMS) will be particularly helpful in implementation at an production site that consists of multiple various machines. The PM items of a machine may vary from cleaning, changing single component, to an overhaul, each with different time interval. By using the IRTMS, the user will have an overview of the PM schedules anytime and anywhere. The preparation of material, components, or tools can be known ahead of time. For simulation purpose, a prototype is constructed by using components as used in industrial real-life condition. Four output connections are provided to simulate the simultaneous monitoring of four machines. The IRTMS prototype is tested and completely successful on doing the running time monitoring, the running time reset, the PM notifications, and the remote access for monitoring and control.